Comparison of Ustad Maulana and Mama Dedeh's Da'wah Strategy: Building Religion in the Era of Globalization through Mass Media - Syarifah, Lailatus; Jannah, Siti Raudhatul; Wazis, Kun (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to compare the preaching strategies of Ustad Maulana and Mama Dedeh in building religiosity in the era of globalization through mass media. This study examines the preaching strategies of Ustad Maulana and Mama Dedeh in building religiosity through mass media, especially the programs "Islam Itu Indah" and "Mamah dan Aa Beraksi." Using a descriptive qualitative approach, this study analyzes the delivery style, humor, language, and interactivity of the two preachers. Data were collected through observation of television broadcasts, interviews, and related literature, then analyzed using the content analysis method to understand the differences and similarities in their preaching strategies. The preaching strategies of Ustad Maulana and Mama Dedeh complement each other in spreading Islamic teachings through mass media. Ustad Maulana uses humor and interactivity to attract the younger generation, while Mama Dedeh applies a more serious rhetorical approach and practical solutions. Both use television effectively, reaching a wide audience with inclusive, flexible, and emotional communication strategies, making preaching more relevant in the era of globalization.